Maturity models of internal quality assurance systems of higher education institutions (Revista Electrónica Calidad en la Educación Superior, 2024)
Internal Quality Assurance Systems in Higher Education Institutions are essential to comply with external accreditation standards and to satisfy stakeholders, so it is necessary to have mature systems that guarantee the fulfillment of these objectives. In this context, a descriptive and documentary research was carried out with the objective of deepening in the existing models to evaluate the maturity levels of management in organizations, which can be applied in Higher Education Institutions, as a background to build a model adjusted to the characteristics of educational institutions in Colombia, which could offer a guide to continuously improve their quality, structure and operation.
Keywords: Models; education quality; quality of education; processes